Data-Screening and Retrieval of Medical Data by the System WAREL - Dorda, W. G. (Methods of Information in Medicine, 1990)
The paper presented here deals with the computer system WAREL, a system for analyzing medical patient data. It is a patientoriented medical data-screening system which automatically points out medical risk factors. Referring to all patients, it is a retrieval system for selecting groups of patients from the clinical data base; the explorative statistical analysis concerning medical data of these selected groups can give an essential impulse to clinical research. The most important components of the system such as the relational data base and the system for defining and activating logical conditions are discussed. These conditions (IF -THEN rules) are the basis of both the patient oriented data-screening and the retrieval of patient groups. They may refer to data in formatted or in natural language form; furthermore conditions of the course of illness can also be formulated. Thus, the data-screeni ng system may also indicate risk situations due to the course of an illness.
Keywords: Clinical Databases; Synchronization Operators; Data Screening; Query Methods